Oriental Philosophical Systems and Work of Iris Murdoch (on the Example of the Novel “The Black Prince”) - R. M. Safiulina (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The subject of study is the originality of the artistic vision of A. Murdoch, which involves in the plot of literary text, the collision and interweaving of various philosophical systems (existentialism, Marxism, Freudianism, neo-Catholicism, pragmatism). The main attention is paid to incorporating Eastern philosophical systems (Zen Buddhism, Sufism) into the work of the writer. The example of the novel “The Black Prince” by A. Murdoch shows the complex interweaving of the life history of the heroes of the work with the philosophical reflections of the author about the laws of the universe, world live order, God, man. The definitions of Zen Buddhism, Sufism, the Sufi Path, as well as the classification of “parking on the Path to the Almighty” are given. The results of a comparative analysis of the novel by A. Murdoch “The Black Prince” and the treatise “Mantiq-ut-tayr” by Sufi author F. Attar are presented. It is proved that Zen Buddhism and Sufism are implanted in the text of the Black Prince novel to create the effect of polyphony of opinions, voices as multidimensionality of being, ambiguity and insufficiency of one interpretation of human actions, as well as any phenomenon in being. An assumption is made about the proximity of the novel “The Black Prince” by A. Murdoch with the theory of Nassim Taleb’s “Black Swan”.